Qualitative-quantitative indicators to regenerate public spaces through Nature-based Solutions - Marco Giampaoletti; Fabrizio Amadei; Maria Michaela Pani (Techne)
The relationship between public works and communities highlights the inherently multidimensional theme of project and evaluation linked to indicators outlined in investment plans and territorial planning. Within this context, the climate crisis necessitates intervention in the city, where public space serves as an intermediate and proximity item, dynamically recalibrating urban interactions among people, nature, and technology. The objective of this paper is to investigate public space, identifying legislative criteria in terms of sustainability and the technological-environmental solutions present in the major environmental certification protocols currently available worldwide, as well as their application in national and international case studies. This analysis allows to define an original framework of dichotomous qualitative-quantitative indicators, simultaneously examining the limitations and future developments of the research. This contribution forms part of the research outcomes undertaken, both completed and ongoing, within the framework of the 2017 PRIN Research “Tech-Start” and the research line Mission 4 – Comp. 2 funded by the NRRP.